The effect of Teucrium polium capsule on pain duration of primary dysmenorrhea - Zahra Shirmohamai Hesari; Farid Zayeri; Khadije Abadian; Zohreh Keshavarz; Maryam Akbari Nozari (Mashhad University of Medical Sciences, 2018)
Introduction: Primary dysmenorrhea is referred to painful menstrual cramps without organic cause, which is one of the most common problems in women of reproductive age. Regarding to high incidence of dysmenorrhea and its effect on daily activities and the side effects chemical drugs, this study was performed with aim to evaluate the effect of Teucrium polium capsule on the pain duration of dysmenorrhea. Methods: This triple-blind controlled randomized clinical trial was conducted on 70 students with primary dysmenorrhea in one of the dormitories of Shahid Beheshti University in 2014. The subjects were randomly divided into intervention and control groups. During the first three days of menstruation, the intervention group was treated with Teucrium polium capsules every 6 hours and the control group with capsules containing starch powder, for two consecutive months. Pain duration was assessed based on the day (one period before the beginning of the study and two periods of intervention). Data analysis was done using SPSS software (version 20) and SAS9.2 software, and independent t-test, Mann-Whitney, and random effects model. P<0.05 was considered significant. Results: There was no significant difference between the two groups in pain duration before the intervention (P > 0.05). The menstrual pain duration significantly decreased after the use of Teucrium polium capsule compared to placebo group (P <0.0001). The pain duration was 4.3 days before the use of Teucrium polium capsule that reduced to 1.9 and 1.4 days after the use of capsule in the first and second periods, respectively. Conclusion: Teucrium polium capsule significantly reduces the menstrual pain duration and can be used to treat primary dysmenorrhea.